PERKAWINAN BELEKET MENURUT ADAT REJANG DI REJANG LEBONG DITINJAU DARI HUKUM ISLAM - Majana, Sanuri (UIN Fatmawati Sukarno Bengkulu, 2017)
The custom is the code of conduct in life that includes real aspect that has been set as custom wedding, this research is the study of shapes of marriage beleket (mating honest) Rejang Rejang Lebong in customs. In this study researchers using this type of research libraries (Library Research). I.e. using techniques of data collection undertaken by way of reading and reviewing some literature or books as well as legislation relating to problems in thorough, as for activities conducted in the analysis of the data, namely: 1. Looking for books to find understanding and laws regulating marriage beleket (mating honest) custom Rejang. 2. Choose the verses of Qur’an and Hadith about marriage as well as books of Fiqh related. 3. create a systematic verses of Qur’an and Hadith and Fiqh books. 4. The Data obtained in the analysis of inductive qualitative basis.The results of this research indicate that: 1. marriage beleket/honest is a form of marriage in the family requires the Rejang, bid pay money to be honest or to the girl leket and in mating beleket/jujurnya big money this honest and much more cakkercik (besides money). honest marriage is a form of marriage eksogami, children then enter klen or bloodlines father, because marriage is a marriage that ensured beleket bloodlines patrlineal.2. in the the purpose of Marriage beleket is equal to marriage in accordance with the concept of marriage in Islam i.e. marriage must be Sekufu described in the Qur’an in Sura An Nur, verse 26 An Nur, verse 3 and Al Hujurat verse 13. In the procession of honest marriage/marriage beleket Rejang Rejang Lebong in customs were in accordance with the marriage in Islam and not against syari ‘, but with a result of beleket in the form of marriage gitie tikea (replace the mat) should be abandoned because it is in the form of the larger tikea gitie mafsadahnya from on maslahah obtained, according to the word of God Saw in Qur’an Sura Al-Baqarah verse and Hadith the Messenger of Almighty, 234. In fostering domestic life forms indigenous beleket Rejang marriage greater mafsadahnya of maslahah in accordance with the Quran, Hadith, Fiqh rules, so that the form of the marriage custom of the Rejang beleket called ‘urf fasid is incompatible with the Islamic Sharia’. The law it is al muharram li Dzatihi